2016
DOI: 10.3390/fib4010001
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Fiber Biocompatibility for Implants

Abstract: Carbon fibers have multiple potential advantages in developing high-strength biomaterials with a density close to bone for better stress transfer and electrical properties that enhance tissue formation. As a breakthrough example in biomaterials, a 1.5 mm diameter bisphenol-epoxy/carbon-fiber-reinforced composite rod was compared for two weeks in a rat tibia model with a similar 1.5 mm diameter titanium-6-4 alloy screw manufactured to retain bone implants. Results showed that carbon-fiber-reinforced composite s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 51 publications
(71 reference statements)
0
43
0
Order By: Relevance
“…Mild toxicity was also reported for CNTs mainly due to oxidative stress and inflammation [ 175 ]. Peterson [ 176 ] conducted an animal study on epoxy/carbon fibre-composite and reported that carbon fibres can undergo osseointegration with live bone.…”
Section: Biomimetic Role Of Hydroxyapatite and Carbon Composite Mamentioning
confidence: 99%
“…Mild toxicity was also reported for CNTs mainly due to oxidative stress and inflammation [ 175 ]. Peterson [ 176 ] conducted an animal study on epoxy/carbon fibre-composite and reported that carbon fibres can undergo osseointegration with live bone.…”
Section: Biomimetic Role Of Hydroxyapatite and Carbon Composite Mamentioning
confidence: 99%
“…As a consequence, they show outstanding mechanical properties along the axis direction but poor mechanical properties in the transverse direction due to the weak van der Waals forces between the layers typical of graphite [360]. Carbon fibers display rather different mechanical properties: tensile strengths from 5.65 to 1.5 GPa and specific modulus from 407 to 106 GPa [360] which may exceed the strength and modulus of steel, 2.39 and 26.6 GPa, respectively [361]. Different types of thermal and stretching treatments can be applied to improve the CF orientation thus increasing the Yang modulus [361].…”
Section: Carbon Fibersmentioning
confidence: 99%
“…Carbon fibers display rather different mechanical properties: tensile strengths from 5.65 to 1.5 GPa and specific modulus from 407 to 106 GPa [360] which may exceed the strength and modulus of steel, 2.39 and 26.6 GPa, respectively [361]. Different types of thermal and stretching treatments can be applied to improve the CF orientation thus increasing the Yang modulus [361]. However, because they are more expensive when compared with other competitors such as glass fibers or plastic fibers, they are used in high performance specialized materials.…”
Section: Carbon Fibersmentioning
confidence: 99%
“…This composition provides excellent mechanical properties, such as high resistance to fatigue, fracture, abrasion and temperature. Moreover, it presents a low specific weight, thermal expansion coefficient, electrical conductivity and a good buffering of vibration forces [ 1 , 2 , 3 , 4 , 5 , 6 ]. CFRC has been mainly used in fixed dental prostheses (FDPs) and framework manufacturing [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%